2013
DOI: 10.1242/jcs.125732
|View full text |Cite
|
Sign up to set email alerts
|

SNX15 links clathrin endocytosis to the PtdIns(3)P early endosome independent of the APPL1 endosome

Abstract: SummarySorting nexins (SNXs) are key regulators of the endosomal network. In designing an RNAi-mediated loss-of-function screen, we establish that of 30 human SNXs only SNX3, SNX5, SNX9, SNX15 and SNX21 appear to regulate EGF receptor degradative sorting. Suppression of SNX15 results in a delay in receptor degradation arising from a defect in movement of newly internalised EGF-receptorlabelled vesicles into early endosomes. Besides a phosphatidylinositol 3-phosphate-and PX-domain-dependent association to early… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
42
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(48 citation statements)
references
References 49 publications
6
42
0
Order By: Relevance
“…Remarkably, PI(3)P-binding SNXs implicated in endosomal sorting and with known localization to early and recycling endosomes, such as SNX1, SNX3, SNX4, SNX8, SNX17 and SNX27, accumulated on TfR clusters in MTM1-depleted cells (Figure 18a, b). In contrast, TfR-cluster were negative for SNX15 (Figure 18a, b), which was previously implicated in earlier sorting events such as the progression of CCVs to PI(3)P-enriched early endosomes (Danson, Brown et al 2013). Many SNXs contain BAR domains with membrane deforming activities (Carlton, Bujny et al 2004), some of which we found enriched on TfR-containing endosomes upon MTM1 depletion.…”
Section: Sub-plasma Membrane Early and Recycling Endosomes Accumulatementioning
confidence: 76%
“…Remarkably, PI(3)P-binding SNXs implicated in endosomal sorting and with known localization to early and recycling endosomes, such as SNX1, SNX3, SNX4, SNX8, SNX17 and SNX27, accumulated on TfR clusters in MTM1-depleted cells (Figure 18a, b). In contrast, TfR-cluster were negative for SNX15 (Figure 18a, b), which was previously implicated in earlier sorting events such as the progression of CCVs to PI(3)P-enriched early endosomes (Danson, Brown et al 2013). Many SNXs contain BAR domains with membrane deforming activities (Carlton, Bujny et al 2004), some of which we found enriched on TfR-containing endosomes upon MTM1 depletion.…”
Section: Sub-plasma Membrane Early and Recycling Endosomes Accumulatementioning
confidence: 76%
“…Each component of this complex has been shown to promote the lysosomal trafficking and degradation of EGFR (Cavet et al, 2008;Chin et al, 2001;Danson et al, 2013;Gullapalli et al, 2004), but this role appears to be independent of their functions within the retromer (Sun et al, 2013a,b); as of yet, it is not clear whether all four SNX proteins function as a complex to regulate EGFR trafficking. SNX5 contains a PX domain and a Bin-amphiphysinRvs (BAR) domain, and its PX domain specifically binds PtdIns(4,5)P 2 (Koharudin et al, 2009).…”
Section: Intracellular Ptdins(45)p 2 Signalingmentioning
confidence: 99%
“…However, SNX20 knock-out mice showed no overt phenotypes related to endothelial cell adhesion, and therefore its precise function is still not clear. Down-regulation of SNX21 by siRNA also has a modest effect on the endocytic degradation of the epidermal growth factor receptor (17), further suggesting a role for these proteins in endosomal transport, although the mechanism underlying this effect has also not been characterized in detail.…”
Section: The Atomic Coordinates and Structure Factors (Code 4ymr) Havmentioning
confidence: 99%